Evaluación de riesgos laborales en las actividades de los trabajadores de la lavadora y lubricadora “CRISAY” del cantón Junín - Ramos Saltos, Nicole Paola (2023)
The objective of this investigation was to evaluate the occupational risks in the activities of the workers of the “Crisay” washing machine and lubricator in Junín canton. The methods used were descriptive and bibliographic, through the application of tools such as direct observation, surveys, interviews and descriptive statistics. Among the results, a diagnosis of the current situation of the work activities of the company's workers was obtained, who perform tasks such as: both complete and express washing, steam washing, vacuuming, polishing and oil changes, with a working day of 08:00 to 17:00 from Monday to Saturday, noting that monthly maintenance is carried out on the work equipment used. The weighting of occupational risks was then carried out using the IPER matrix where, once identified, the probability and impact that the risks associated with the activities have on the workers were analyzed; it was found that ergonomic and mechanical risks obtained a high level within this weighting, being considered the most relevant. Based on this information, a comprehensive occupational risk prevention plan was developed in accordance with the guidelines of the Ministry of Labor in Ecuador, in order to provide knowledge about the correct management of occupational health and safety, through socialization of the comprehensive plan content through training talks and delivery of informative material to staff.